Study of medicinal plants in the metropolitan area of Saltillo, Coahuila, Mexico - Lara Reimers, Eduardo Alberto; Gómez Ugues, Diana Marlene; Uresti Duran, Diana; Encina Domínguez, Juan A; Peña Ramos, Fidel M (Ecosistemas y Recursos Agropecuarios, 2023)
Since ancient times, man's relationship with natural resources has been very close, especially in the use of plants, whether as food, clothing, construction material or to cure illnesses and physical injuries. The objective of this study was to record some of the uses of the most common medicinal plants and the most frequent conditions in the metropolitan area of Saltillo, Coahuila. From October 2021 to May 2022, 113 informants (17 men and 96 women, aged 20 to 70 years) were interviewed through a semi-structured ethnobotanical questionnaire divided into two parts: socioeconomic aspects and traditional knowledge of medicinal plants. The use report obtained was divided into 13 main categories based on the International Statistical Classification of Diseases and Health Problems of the World Health Organization. Registered an average of 4.6 plants and five uses per plant. According to gender, women registered 4.9 plants on average, compared to men with 3.1. The simple regression analysis, shows positive correlation between Age and Plant Number. They reported the use 82 plants to treat diseases, belonging to 37 botanical families. The diseases that most frequently affect the interviewees are those that affect the respiratory, gastrointestinal and nervous systems. The medicinal species with the highest Use Value Index were: Matricaria chamomilla (IVU=0.65) and Litsea parvifolia (IVU=0.35). While the most representative families were Asteraceae (10 species, 125 use reports), Lamiaceae (12 species, 119 RU) and Lauraceae (four species, 64 RU). The most common form of preparation was infusion (88.6 %) and poultice (3.68 %).
Keywords: Asteraceae; Traditional knowledge; Ethnobotany; Matricaria chamomilla; Respiratory system